Portal vein thrombosis after double installation of transjugular intrahepatic portosystemic stent (clinical observation) - M. S. Guska; A. D. Kuznetsova; B. I. Kazymov; K. F. Alekberov; Z. G. Kaziakhmedova; B. I. Yaremin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Relevance. Liver transplantation involves reconstruction of several vascular structures. Portal reconstruction presents many difficulties due to the frequent intraoperative detection of thrombosis. Portal vein thrombosis is a condition caused by stagnation of blood flow, vascular injury, or hypercoagulability, leading to partial or complete occlusion of the portal vein. The prevalence of thrombosis ranges from 2.1 to 23.3% among liver transplant candidates without hepatocellular cancer. According to autopsy data, the incidence of thrombosis in liver cirrhosis is 6– 64%.Purpose: to analyze a case of portal vein thrombosis in a patient with two preliminary attempts to install transjugular intrahepatic portosystemic stents and their thrombosis.Materials and methods: a clinical case of thrombosis of the stent and portal vein in a 53-year-old patient with decompensated liver cirrhosis as a result of viral hepatitis C with portal hypertension. The peculiarity of this case is that after double transjugular intrahepatic portosystemic stenting, thrombosis of the venous vein was detected only intraoperatively. A liver transplant was performed; the functionality of the graft was not impaired.Conclusion. This case illustrates the need for future research on the topic of portal vein thrombosis and techniques for identifying it preoperatively.